Analyzing Laptop Brand Positioning in Indonesia: A Perceptual Mapping Approach - Adinda, Citra; Syahira, Rivana; Risde, Kahti Ramadhia; Rahayu, Fatik (Golden Ratio of Mapping Idea and Literature Format, 2026)
The rapid growth of Indonesia's laptop market has intensified competition among brands like ASUS, Lenovo, Acer, HP, and Axioo, necessitating effective positioning strategies to capture consumer preferences. This study aims to identify key attributes influencing consumer perceptions, analyze the positioning of these five laptop brands, and propose strategies to enhance their competitiveness. Using discriminant analysis and perceptual mapping, data were collected from 150 respondents via online surveys, focusing on attributes such as price, performance, design, screen quality, battery life, weight, and service center availability. Findings reveal that screen quality (dimension one, -0.83) and performance (dimension two, 0.873) are the most critical attributes. ASUS emerges as the market leader, excelling in screen quality, performance, service center, and weight. At the same time, Lenovo leads in price and battery life, Acer in performance, and Axioo and HP in screen quality and weight. Recommendations include ASUS improving design and battery life, Axioo enhancing performance and service centers, Lenovo upgrading design and performance, Acer addressing price and battery life, and HP focusing on performance and service accessibility. This research contributes to marketing literature on brand positioning and offers managerial insights for strengthening brand competitiveness in Indonesia's dynamic laptop market.